İLAÇ MÜMESSİLLERİNİN ÖRGÜTSEL BAĞLILIĞININ, İŞ TATMİNİNİN VE İŞTEN AYRILMA NİYETİNİN DEMOGRAFİK FAKTÖRLER BAĞLAMINDA İNCELENMESİ. - VAROL, Fatih; KARAER, Memiş; ORTAKARPUZ, Metehan (Electronic Turkish Studies)
Concepts such as organizational commitment, job satisfaction, and intention to leave job are the focus of researchers for many years. Relevant literature reveals various findings in relation to these concepts. In the light of these discussions, what kind of relationship will there be between organizational commitment, job satisfaction and intention to leave job and how this relationship structure will be shaped for pharmaceutical sector employees is a matter to be investigated. The aim of this research is to identify the relationship between the demographic characteristics of the pharmaceutical sector employees in Konya province and the intentions of organizational commitment, job satisfaction and intent to leave job. Approximately all of the datas, which is needed to, was obtained by making face to face conversation with the method of survey. At the stage of data collection, 202 of 245 surveys which was delated out to the pharmaceutical sector employees, turned back and 196 of these surveys were approved to the assessment. Datas obtained in the research were examined with the help of SPSS 22.0 package programme; reliability and validity, t-test, one way variance (ANOVA) analyzes were performed. According to the findings, there is a significant relationship between normative commitment and age groups. There is a significant relationship between all components of organizational commitment and income level. There is no significant relationship between demographic characteristics and intention to leave job.